2013
DOI: 10.14742/ajet.191
|View full text |Cite
|
Sign up to set email alerts
|

iArchi[tech]ture: Developing a mobile social media framework for pedagogical transformation

Abstract: This paper critiques the journey of pedagogical change over three mobile learning (mlearning) project iterations (2009 to 2011) within the context of a Bachelor of Architecture degree. The three projects were supported by an intentional community of practice model involving a partnership of an educational researcher/technologist, course lecturers, and course students. The pedagogical changes achieved over three years of sustained collaborative participatory action research illustrate the potential for using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The students researched how to design the structure of a successful survey, how many parts the survey should have, how many questions, and what type of answers to look for (open-ended, numerical, Likert scale). The survey was designed in Google Forms and consisted of 49 questions that contained four sections: (1) The first aimed at revealing the demographic profile of the respondent (questions 1-11); (2) the second aimed at uncovering habits related to the use of public spaces (questions 12-24); (3) the third aimed at deciphering local social relations (questions 25-34); and (4) the fourth focused on specific public space features considered important or key for the respondent in public space design (questions [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Design Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The students researched how to design the structure of a successful survey, how many parts the survey should have, how many questions, and what type of answers to look for (open-ended, numerical, Likert scale). The survey was designed in Google Forms and consisted of 49 questions that contained four sections: (1) The first aimed at revealing the demographic profile of the respondent (questions 1-11); (2) the second aimed at uncovering habits related to the use of public spaces (questions 12-24); (3) the third aimed at deciphering local social relations (questions 25-34); and (4) the fourth focused on specific public space features considered important or key for the respondent in public space design (questions [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Design Of the Methodsmentioning
confidence: 99%
“…In an increasingly networked society, where proximity is not anymore relevant for the social organization [44], social media can be a powerful tool for collaborative learning and production. Cochrane and Rhodes concluded that mobile learning provides a fruitful student-directed collaboration enabled by the unique features of social media [45]. A study by Smith [30] envisions architecture students as possible prodigies of the planning workshops, however, assigns them a marginal role in drafting or "innovation through drawing".…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to successfully adopt mobile learning in educational institutions, several factors have been listed in the studies. These factors may be listed as technical competence of learners, user-friendly design, learner community development and platform accessibility [54,[68][69][70][71][72][73]. The authors of [68] focused on the mobile social media framework.…”
Section: Csfs Related To Mobile Learningmentioning
confidence: 99%
“…These factors may be listed as technical competence of learners, user-friendly design, learner community development and platform accessibility [54,[68][69][70][71][72][73]. The authors of [68] focused on the mobile social media framework. They called them mobile social media CSFs that included six factors, namely "pedagogical integration of the technology into the course and assessment, lecturer modeling of the pedagogical use of the tools, creating a supportive learning community, appropriate choice of mobile devices and web 2.0 social software, technological and pedagogical support, and creating sustained interaction that facilitates the development of ontological shifts, both for the lecturers and the students".…”
Section: Csfs Related To Mobile Learningmentioning
confidence: 99%
“…Such a change is not simple though because it requires broader understandings of what PLD should be and what it should provide. Research supports the idea that learning can be enhanced by using information and communications technologies (ICT), in particular, social networking tools that provide a heterogeneous system accessible through a variety of mobile devices (Cochrane and Rhodes 2013). When PLD provision exploits the affordances of a virtual environment to combine virtual mentoring with an online Community of Practice (CoP), education practitioners can be supported, within their own context (location), to apply, build and shape their knowledge and skills, at a time that suits them.…”
Section: Introductionmentioning
confidence: 97%